Penyuaraan Pesan Teks Media Sosial Pada Perangkat Mobile Menggunakan Text To Speech - Michael Alexander Rustan; Anita Nathania Purbowo; Liliana Liliana (Jurnal Infra, 2022)
The use of smartphones as a communication tool will increase along with the increase of smartphone users. Based on the data obtained, in early 2021 there are around 167 million smartphone users in Indonesia. The use of smartphone as a communication tool to send messages in its use can also start to annoy people when they are doing activities that require concentration, for example, such as driving. In 2017, there were about 15,341 cases of accidents in America caused by drivers using smartphone. To overcome this problem, the text to speech feature will be used to voicing the incoming messages so smartphone users do not need to open their smartphone to find out the sender and the contents of the message. The results of the tests that carried out on the usage on text to speech feature showed that the system can voiced the incoming messages well. For messages that have abbreviated words, the text to speech feature cannot voiced them properly. As for the tests carried out on the feature to detect the message, the system can detect some message data such as the package name of the application, the sender's name, and also the message content properly. For messages received through group chat, the detection results from the line application, and the whatsapp application have problems, so there are obstacles in the process of voicing group chat messages on the line application and whatsapp applications.